Medical Tourist's Perception in Selecting their Destination: A Global Perspective - Noorhazilah A Manaf; Abdullah AM Sarwar; Azura Omar (Tehran University of Medical Sciences, 2012)
Background: The need for better healthcare has grown significantly in recent years. In addition, the rising healthcare costs in the U.S. and in many European countries have forced many patients to seek medical treatment abroad, which has created the demand for medical tourism. With little yet known as to the perception of a medical tourist's destination selection, this study aims to explore medical tourist's perception in selecting their destination while going for medical treatment.Methods: Realizing the current need to examine closely the perception of medical tourists, this study had conducted a secondary study to collect data for assessing and identification of the key factors on patient's perception and destination selection criteria.Results: The result confirms the existence of a very strong relationship between cost, service quality, treatment types and availability and marketing impact on the perception of the medical tourists' in selecting their medical tourism destination.Conclusion: This study offers support for the proposed conceptual model and an empirical basis for comparison in future research.